1988
DOI: 10.1021/bi00422a013
|View full text |Cite
|
Sign up to set email alerts
|

Base-sequence dependence of noncovalent complex formation and reactivity of benzo[a]pyrenediol epoxide with polynucleotides

Abstract: The base-sequence selectivity of the noncovalent binding of (+/-)-trans-7,8-dihydroxy-anti-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyr ene (BPDE) to a series of synthetic polynucleotides in aqueous solutions (5 mM sodium cacodylate buffer, 20 mM NaCl, pH 7.0, 22 degrees C) was investigated. The magnitude of a red-shifted absorbance at 353 nm, attributed to intercalative complex formation, was utilized to determine values of the association constant Kic. Intercalation in the alternating pyridine-purine polymers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 64 publications
8
58
1
Order By: Relevance
“…Most relevant to the present study, it has been shown through computational analyses (44) that cytosine methylation affords an increased helical stability resulting in increased hydrophobicity and molecular polarizability (51), and it may be these characteristics that lead to the increased reactivity of BPDE at these sites. In agreement with this prediction, the presence of multiple 5-methylcytosines in duplex DNA were shown to result in greater levels of noncovalent intercalation (52). Since BPDE is believed to first intercalate with DNA prior to forming a covalent adduct, an increase in intercalation or an altered structure may lead to the preferential modification seen in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Most relevant to the present study, it has been shown through computational analyses (44) that cytosine methylation affords an increased helical stability resulting in increased hydrophobicity and molecular polarizability (51), and it may be these characteristics that lead to the increased reactivity of BPDE at these sites. In agreement with this prediction, the presence of multiple 5-methylcytosines in duplex DNA were shown to result in greater levels of noncovalent intercalation (52). Since BPDE is believed to first intercalate with DNA prior to forming a covalent adduct, an increase in intercalation or an altered structure may lead to the preferential modification seen in this study.…”
Section: Discussionsupporting
confidence: 82%
“…17,20,21,51,52 While this view has been challenged, 53,54 there is accumulating in vitro evidence that the methylation of cytosine in CpG dinucleotide steps indeed enhances the reactivity of B[a]PDE with the guanine residue in meCpG sequence contexts. 23,24,26,55,56 This effect is most likely associated with the hydrophobicity of the methyl group that enhances both the non-covalent intercalative binding of B[a]PDE to double-stranded poly(dG-me dC)·poly(dG-me dC) and the subsequent yield of covalent [BP]G adduct formation 55,57 as observed in p53 oligonucleotide sequence 17,20,21,23,24,26 and other sequence contexts. 25 …”
Section: Discussionmentioning
confidence: 99%
“…BPDE forms noncovalent intercalative complexes with double-stranded DNA that are thought to precede covalent binding of BPDE to DNA (51). It has previously been reported that methylation of the 5 position of cytosine gives rise to an enhancement of intercalative BPDE binding to the synthetic polymer poly(dG-dC)⅐(dG-dC) (52). Hydrophobic effects (52) or increased molecular polarizability and base stacking (53) derived from the methyl group may facilitate the creation of an intercalation site for BPDE.…”
Section: Discussionmentioning
confidence: 99%